Seeing disadvantage in schools: exploring student teachers' perceptions of poverty and disadvantage using visual pedagogy. Issue 4 (7th August 2016) - White, M. L.; Murray, Jean
Abstract: This paper describes exploratory research into the development of innovative visual pedagogies for investigating how pre-service student-teachers articulate their views about the effects of poverty on educational attainment. Social class emerges as the strongest factor in poverty and educational disadvantage in the UK. The resulting issues are often awkward for students to discuss and conventional pedagogies may not have effective 'reach' here. Findings from this study showed that the visual methods deployed gave students pedagogically well-structured spaces for the expression and exchange of a diversity of views about poverty and social class, engaging them in both heated discussions and prolonged 'silences'. However, the pedagogies did not challenge the stereotypical deficit models of 'the poor' which some students expressed. Nevertheless, we argue that reconfigured versions of these visual pedagogies have considerable potential for innovative social justice work in teacher education.